2022
DOI: 10.3389/fonc.2022.842356
|View full text |Cite
|
Sign up to set email alerts
|

Fbw7 Inhibits the Progression of Activated B-Cell Like Diffuse Large B-Cell Lymphoma by Targeting the Positive Feedback Loop of the LDHA/lactate/miR-223 Axis

Abstract: BackgroundF-box and WD repeat domain-containing 7 (Fbw7) is well known as a tumor suppressor and ubiquitin ligase which targets a variety of oncogenic proteins for proteolysis. We previously reported that Fbw7 promotes apoptosis in diffuse large B-cell lymphoma (DLBCL) through Fbw7-mediated ubiquitination of Stat3. This study aimed to identify the mechanism of Fbw7-mediated aerobic glycolysis reprogramming in DLBCL.MethodsExpression levels of Fbw7 and Lactate Dehydrogenase A (LDHA) in human DLBCL samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…86 It has been shown that the inactivation of FBW7-mediate degradation of lactate dehydrogenase A (LDHA) promoted large B-cell lymphoma tumor progression in vivo and in vitro. 87 Further, in adult T-cell leukemia-lymphoma, FBW7 repressed Notch signaling and hindered tumor growth. 88 However, contradictory reports exist concerning the role of FBW7 in cancers.…”
Section: Ubiquitin Ligases (E3s)mentioning
confidence: 99%
See 1 more Smart Citation
“…86 It has been shown that the inactivation of FBW7-mediate degradation of lactate dehydrogenase A (LDHA) promoted large B-cell lymphoma tumor progression in vivo and in vitro. 87 Further, in adult T-cell leukemia-lymphoma, FBW7 repressed Notch signaling and hindered tumor growth. 88 However, contradictory reports exist concerning the role of FBW7 in cancers.…”
Section: Ubiquitin Ligases (E3s)mentioning
confidence: 99%
“…Likewise, FBW7 has been demonstrated to inhibit tumor growth in the lung, thyroid, melanoma, and cervical cancer 86 . It has been shown that the inactivation of FBW7‐mediate degradation of lactate dehydrogenase A (LDHA) promoted large B‐cell lymphoma tumor progression in vivo and in vitro 87 . Further, in adult T‐cell leukemia‐lymphoma, FBW7 repressed Notch signaling and hindered tumor growth 88 .…”
Section: The Role Of Ups Dysregulation In Tumorigenesismentioning
confidence: 99%
“…Inhibition of LDHA can limit the energy supply in cancer cells, thereby reducing metastasis and invasion of cancer cells 17 . Many studies have suggested that LDHA is a prognostic factor and a potential target for treatment in DLBCL [18][19][20][21][22] . Metabolism-related gene LDHA was highly expressed in malignant B cells in DLBCL tissue which was clustered using scRNA-seq 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic glycolysis is the primary pathway by which tumor cells utilize glucose, known as the Warburg effect 12 , 13 . Numerous studies have indicated that tumor cells modulate the expression of glycolysis-related proteins through ubiquitin modification, thereby activating or inhibiting the glycolytic pathway 14 , 15 , 16 . For instance, the E3 ligase Fbw7 inhibits glycolysis in diffuse large B-cell lymphoma by promoting the ubiquitin-mediated degradation of LDHA 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that tumor cells modulate the expression of glycolysis-related proteins through ubiquitin modification, thereby activating or inhibiting the glycolytic pathway 14 , 15 , 16 . For instance, the E3 ligase Fbw7 inhibits glycolysis in diffuse large B-cell lymphoma by promoting the ubiquitin-mediated degradation of LDHA 14 . HectH9, through K63-linked ubiquitination, facilitates the transfer of HK2 to mitochondria and enhances glycolysis in prostate cancer 15 .…”
Section: Introductionmentioning
confidence: 99%